George Washington Carver, what do you see? - Benge, Janet, 1958-; Benge, Geoff, 1954-; James, Kennon (Houston : Advance Pub., 1997)
A brief biography of the African American scientist who overcame tremendous hardship to make unusual and important discoveries in the field of agriculture.
Keywords: Carver, George Washington, -- 1864?-1943 -- Juvenile literature; Carver, George Washington, -- 1864?-1943.; African American agriculturists -- Biography -- Juvenile literature; Agriculturists -- United States -- Biography -- Juvenile literature; African Americans -- Biography; Agriculturists